Coordinative patterns between carving turn and skidding turn during alpine skiing - Kim, J.-N.; Lim, H.-S.; Park, S.-H.; Jeong, C.-H.; Yoon, S.-H. (ISBS Proceedings Archive (Michigan), 2018)
The purpose of this study was to investigate the coordinative patterns between segments and ski using the continuous relative phase (CRP) on anteroposterior and vertical axis during carving and skidding turn. Fourteen alpine ski instructors were participated in this study. Eight inertial measurement units were used to collect segment kinematic data. Each skier was asked to perform ten carving turns and ten skidding turns on the groomed 15° slope, respectively. CRP angles between all segments and ski were significantly increased during carving turn on the vertical axis. On the other hand, CRP angles between all segments and ski were significantly increased during skidding turn on anteroposterior axis. Therefore, skiers should perform the anti-phase movements of the lower spine-ski, pelvis-ski, thigh-ski and shank-ski on the vertical axis during the carving turn and the in-phase movements of the lower spine-ski, pelvis-ski, thigh-ski and shank-ski on the anteroposterior axis during skidding turn.